Analisis Kesulitan Belajar Membaca (Disleksia) dan Kesulitan Belajar Menulis (Disgrafia) Siswa Kelas I SDN Tanah Tinggi 3 Tangerang - Nurfadhillah, Septy; Saridevita, Alviani; Adji, Aris Setiawan; Valentina, Febi Ria; Astuty, Herlin Wizy; Devita, Nanda; Destiyantari, Sagita (MASALIQ, 2022)
Learning difficulties are a condition in which students do not learn properly because there are certain disorders. This study aims to analyze reading difficulties (dyslexia) and writing difficulties (dysgraphia) in the first grade of elementary school. The research method used is descriptive qualitative. The subjects of this study were first grade students at Tanah Tinggi 3 Elementary School, Tangerang City, totaling 1 person and first grade teachers. The data collection procedures used were observation, interviews and documentation. The results showed that the first grade students of 24 students had difficulty learning to read (Dyslexia) and difficulty learning to write (Dysgraphia). The results showed that difficulties in learning to read (Dyslexia) and difficulties in learning to write (Dysgraphia) that occurred in grade I included slow writing, errors in writing the letters of the alphabet, stammering in reading caused because students had not memorized the letters of the alphabet, lacked comprehension skills. respond to questions from the teacher and hesitate to answer questions from the teacher.